Pengaruh Penerapan E-Registration, E-Billing, E-Filing terhadap Kepatuhan Wajib Pajak pada Kantor Pelayanan Pajak (KPP) Pratama Bulukumba - Nurannisa Nurannisa (International Forum of Researchers and Lecturers, 2026)
This study aims to: (a) examine the partial influence of the E-Registration system on individual taxpayer compliance at KPP Pratama Bulukumba, (b) assess the influence of the E-Billing system on individual taxpayer compliance, and (c) determine the partial influence of the E-Filing system on individual taxpayer compliance at the same tax office. The population of this research consists of individual taxpayers registered in 2023, totaling 182,071 at KPP Pratama Bulukumba. The sample comprises 99 individual taxpayers who utilize E-Registration, E-Billing, and E-Filing systems in fulfilling their tax obligations. The sampling method employed is purposive sampling, based on specific criteria. Data were collected using a structured questionnaire. The data analysis involved data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results indicate that: (1) E-Registration has a positive and significant effect on individual taxpayer compliance, (2) E-Billing has a positive and significant effect on individual taxpayer compliance, and (3) E-Filing has a positive and significant effect on individual taxpayer compliance at KPP Pratama Bulukumba.